Earning Per Share dalam Memoderasi Intellectual Capital dan Return On Asset terhadap Nilai Perusahaan - Setyowati Setyowati (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study explores whether Earnings per Share (EPS) plays a role in shaping how Intellectual Capital (IC) and Return on Assets (ROA) influence firm value in the banking sector over the 2018 2022 period. It focuses on nine BUKU 4 banks listed on the Indonesia Stock Exchange (IDX) and relies on secondary data. A quantitative approach is applied, with analysis carried out using Partial Least Squares (PLS) through SmartPLS 4. The findings show that ROA has a positive and significant effect on firm value, indicating that stronger profitability tends to be followed by higher market valuation. In contrast, EPS is found to have a negative and significant direct effect on firm value. When examined as a moderating variable, EPS strengthens the relationship between intellectual capital and firm value, suggesting that higher earnings can amplify the contribution of intangible resources. However, EPS weakens the effect of ROA on firm value, as reflected in its negative and significant moderating role. Overall, these results point to the nuanced role of EPS beyond its direct impact in shaping how internal capabilities and financial performance are translated into firm value within large Indonesian banks.